2017
DOI: 10.1186/s12935-017-0434-6
|View full text |Cite
|
Sign up to set email alerts
|

HOTAIR: a key regulator in gynecologic cancers

Abstract: Long non-coding RNAs (lncRNAs) play critical roles in the initiation and progression of human cancers. HOX transcript antisense RNA (HOTAIR) is an lncRNA localized to the mammalian HOXC gene cluster; it can interact with polycomb repressive complex 2 and the lysine-specific histone demethylase/CoREST/REST complex, and it manipulates the expression of various genes. HOTAIR promotes tumor invasion and metastasis by silencing tumor suppressors, and activating oncogenes and signaling pathways. HOTAIR is deregulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“… 4 lncRNA HOTAIR is related to gynecologic cancer cell radioresistance. 5 lncRNA UCA1 can increase prostate cancer radioresistance. 6 A num ber of studies 7 , 8 about PC have demonstrated that lncRNA can promote PC genesis and development, such as lncRNA UCA1, lncRNA DUXAP10, and lncRNA HOTAIR.…”
Section: Introductionmentioning
confidence: 99%
“… 4 lncRNA HOTAIR is related to gynecologic cancer cell radioresistance. 5 lncRNA UCA1 can increase prostate cancer radioresistance. 6 A num ber of studies 7 , 8 about PC have demonstrated that lncRNA can promote PC genesis and development, such as lncRNA UCA1, lncRNA DUXAP10, and lncRNA HOTAIR.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA HOTAIR (HOX transcript antisense RNA) was the first trans-acting lncRNA gene to be discovered in a range of cancers [22,23], and its upregulation is predictive of decreased survival in a variety of tumor cells [24,25]. Lysine specific demethylase 1 (LSD1) and polycomb repressive complex 2 (PRC2) are functional targets of HOTAIR and it is thought that HOTAIR may serve as scaffold for LSD1 and PRC2.…”
Section: Classical Oncogenic Lncrnas In Gscsmentioning
confidence: 99%
“…B. of HOTAIR is associated with metastatic progression and low survival rates in breast, colon and liver cancer patients [14,20,27,49,8,53,41,43,25]. The complete list of sponge interactions whose members exhibit such spatial proximity at least between two RNAs in the sponge are provided in Supp.…”
Section: Spatially Proximal Cernas Interactionsmentioning
confidence: 99%